American Heart Association's Life Simple 7 and Risk of Atrial Fibrillation in a Population Without Known Cardiovascular Disease: The ARIC (Atherosclerosis Risk in Communities) Study. Issue 8 (12th April 2018) - Garg, Parveen K.; O'Neal, Wesley T.; Chen, Lin Y.; Loehr, Laura R.; Sotoodehnia, Nona; Soliman, Elsayed Z.; Alonso, Alvaro
Abstract : Background: The American Heart Association has defined metrics of ideal cardiovascular health known as Life's Simple 7 (LS7) to prevent cardiovascular disease. We examined the association between LS7 and incident atrial fibrillation (AF) in a biracial cohort of middle‐ and older‐aged adults without known cardiovascular disease. Methods and Results: This analysis included 13 182 ARIC (Atherosclerosis Risk in Communities) study participants (mean baseline age=54±5.7 years; 56% women; 25% black) free of AF and cardiovascular disease. An overall LS7 score was calculated as the sum of the LS7 component scores and classified as inadequate (0‐4), average (5‐9), or optimal (10‐14) cardiovascular health. The primary outcome was incident AF, identified primarily by ECG and hospital discharge coding of AF through December 31, 2014. A total of 2266 (17%) incident AF cases were detected over a median follow‐up of 25.1 years. Compared with the inadequate category (n=1057), participants in the average (n=8629) and optimal (n=3496) categories each had a lower risk of developing AF in a multivariable Cox proportional hazards model (hazard ratio 0.59, 95% confidence interval 0.51, 0.67 for average; and hazard ratio 0.38, 95% confidence interval 0.32, 0.44 for optimal). In a similar model, a 1‐point‐higher LS7 score was associated with a 12% lower risk of incident AF (hazard ratio 0.88, 95% confidence interval 0.86, 0.89). Conclusions: A higher LS7 score is strongly associated with a lower risk of AF in individuals without baseline cardiovascular disease. Determining whether interventions that improve the population's cardiovascular health also reduce AF incidence is needed.